Study on the Aral Sea crisis from the risk assessment of polycyclic aromatic hydrocarbons and organochlorine pesticides in surface water of Amu Darya river basin in Uzbekistan - Jin, Miao; Wu, Jinglu; Zhang, Hongliang; Zhao, Zhonghua; Alam, Manawwer; Guo, Ru (Frontiers in Earth Science, 2023)
The Amu Darya River, as one of the important flows of the Aral Sea located in the semi-arid area of Central Asia, also performed as the primary water supply for Uzbekistan. Therefore, the residues and risks of anthropogenic-related persistent organic pollutants (POPs) in waters of the Amu Darya River were conducted in the present study to elucidate their possible effects on the water safety in such a specific area as well as on the Aral Sea Crisis from a new perspective. Thirty-nine water samples distributed along the Amu Darya River to the coastal of the Aral Sea were analyzed for both polycyclic aromatic hydrocarbons (PAHs) and organochlorine pesticides (OCPs) occurrence, showing the total concentrations of ΣOCP and ΣPAH in the range of 1.16-22.75 ng/L and 3.18-506.26 ng/L, respectively. Spatial differences showed higher levels for both OCPs and PAHs along the lower reaches of the Amu Darya River due to intense human activities. Source identification performed by isomer ratios indicated that dichlorodiphenyltrichloroethanes (DDTs) probably originated from recent use, while hexachlorocyclohexanes (HCHs), chlordanes, and endosulfans originated mainly from historical usage. Furthermore, the principal component analysis showed PAHs were from coal and petroleum combustion (65.2%), biomass combustion (27.2%), and industrial chemical combustion (7.64%). The human health risk assessment demonstrated no carcinogenic or non-carcinogenic risks at present. However, moderate to high ecological risks to aquatic organisms especially were observed along the lower reaches, especially the delta area. The results obtained would not only provide 2 important basic data for such a semi-arid area but also show us the possible toxic effects induced by such pollutants, which should attract more attention in the shrinking case of the Aral Sea.